The evolution of a Lollard book of instruction : a critical edition of material from Trinity College Dublin MS 245 - Hulsman, Gregory (Trinity College (Dublin, Ireland). School of English, 2015)
This is a critical edition of material from Trinity College Dublin MS 245, an early fifteenth-century Lollard instructional anthology. This thesis will be a case study, the aim of which is to reassess the nature of such anthologies by considering one individual manuscript as a book in and of itself, something which has not yet been done. There will be an analysis of the manuscript's history, particularly its evolution over time, which saw the later addition of a quire, and special attention is paid to the texts in their original context, i.e. in relation to one another. There follows a transcription, complete with extensive annotations, of a selection of the texts (the reasons for the omission of certain tracts are explained fully in the section entitled 'Editorial Practice'). The analysis of the manuscript is in two parts. Firstly, the contents of the original structure, which the compiler carefully selected, prior to the addition of the first quire, are discussed in detail. The emphasis is on the role of the compiler, so the layout of the texts, and the ways in which they relate to one another, is covered, before they are put into the broader context with a discussion of their place within the contemporary theological spectrum. The central themes of Church corruption, social unrest, and the presence of Antichrist on Earth, are then examined, with the conclusion being drawn that the compiler's motivation was to warn the faithful of the imminent apocalypse. Secondly, there is an analysis of the first quire, with attention again being paid to the layout of the texts and how they relate to one another. The discussion revolves around both the restructuring of the manuscript, and the specific four texts of the first quire, and how these helped to refocus the purpose of the anthology. In light of this, the manuscript is considered as a book of instruction with the specific aim not of education, but rather, re-education. This is achieved by the addition of the four texts which help to reshape the anthology's structure so that it mirrors that of the primer. The sense of urgency concerning the approach of Judgement Day remains, but is significantly toned down, with the compiler introducing a nuanced instructional approach, likely informed by a desire to lead the faithful back to Christ. No evidence for basic Lollard educational practices exists, with everything pointing toward an advanced exegetical programme, of which MS 245 is an example. Thus, it is argued that Lollard schools did not provide basic education, but rather, built upon orthodox foundations. The aim was to demystify Scripture, to remove the complexities of devotional practice, to dismantle that which the institutional Church had built, and ultimately to re-educate the faithful in God's word. In the context of MS 245, to base the structure of the anthology on that of the primer demonstrates the compiler's awareness of both the benefits of orthodox pedagogical practices, and where he believed the institutional Church had failed. The Church had armed the laity with a basic knowledge of Scripture, but kept deeper understanding at arm's length, while gradually leading followers away from Christ. Thus, the ultimate aim of the compiler was two-fold; to effectively assert lay authority and the importance of vernacular theology, and to facilitate the re-education, and salvation, of the faithful by carefully rooting the book in orthodox tradition.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin